Effects of N-Acetylcysteine and N-Acetylcysteine Amide on Erythrocyte Deformability and Oxidative Stress in a Rat Model of Lower Extremity Ischemia-Reperfusion Injury - Gokhan Erol; Hakan Kartal; Faruk M. Comu; Erdem Cetin; Ertan Demirdas; Huseyin Sicim; Celal S. Unal; Celalettin Gunay; Bilgehan S. Oz; Cengiz Bolcal (Cardiology Research and Practice)
N-acetylcysteine (NAC) is an antioxidant which works as a free radical scavenger and antiapoptotic agent. N-acetylcysteine-amide (NACA) is a modified form of NAC containing an amide group instead of a carboxyl group of NAC. Our study aims to investigate the effectiveness of these two substances on erythrocyte deformability and oxidative stress in muscle tissue. Materials and Methods. A total of 24 Wistar albino rats were used in our study. The animals were randomly divided into five groups as control (n: 6), ischemia (n: 6), NAC (n: 6), and NACA (n: 6). In the ischemia, NAC, and NACA groups, 120 min of ischemia and 120 min of reperfusion were achieved by placing nontraumatic vascular clamps across the abdominal aorta. The NAC and NACA groups were administered an injection 30 min before ischemia (100 mg/kg NAC; 100 mg/kg NACA; intravenous). Blood samples were taken from the animals at the end of the ischemic period. The lower extremity gastrocnemius muscle was isolated and stored at −80 degrees to assess the total antioxidant status (TAS), total oxidant status (TOS), and oxidative stress index (OSI) values and was analyzed. Results. The erythrocyte deformability index was found to be statistically significantly lower in rats treated with NAC and NACA before ischemia-reperfusion compared to the groups that received only ischemia-reperfusion. In addition, no statistically significant difference was found between the control group and the NAC and NACA groups. The groups receiving NAC and NACA before ischemia exhibited higher total antioxidative status and lower total oxidative status while the oxidative stress index was also lower. Conclusion. The results of our study demonstrated the protective effects of NAC and NACA on erythrocyte deformability and oxidative damage in skeletal muscle in lower extremity ischemia-reperfusion. NAC and NACA exhibited similar protective effects on oxidative damage and erythrocyte deformability.